MEASURING THE LEVEL OF BODY QUALIFICATION BY INDICATING SOME MUSCLE FATIGUE VARIABLES AS WELL AS FUNCTIONAL INDICATORS VARIATIONS - Assistant Professor Doctor. Haider Majeed Hameed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Relationship of some variables of muscle fatigue with physical efficiency and some functional indicators .It includes four Chapters, including the first section on the introduction and the importance of research as the state of fatigue is the lack of energy stored in the muscle and increasing in the accumulation of brownic acid, so the problem of the research which impedes the work of muscle contraction by the relationship between some variables of muscle fatigue physical efficiency and some functional indicators for students in the first year on college, The most important results obtained in the study were that there is a correlation between the fatigue index and physical efficiency as well as between the fatigue index and the maximum consumption of oxygen.The Relation between muscles fatigue parameter & Physical Working Capacity & VO2max. The aim of the research is study The Relation between muscles fatigue parameter & Physical Working Capacity & VO2max to the first stage student of the collage we are choose (11) players who play at local competition of the collage & the most texts are PWC 170 & Carlson & VO2max. The most results of this research are there are good relationship between muscles fatigue (Carlson) & Physical Working Capacity & Carlson & VO2max.